Use of reclaimed fly ash for the production of sustainable cementitious composites - Delgado García, Tomás; Figueroa Altschwager, José Ignacio; Paul, Alvaro (Revista Ingeniería de Construcción, 2024)
This study analyzes the use of reclaimed fly ash (RFA) as an alternative cementitious material in engineered cementitious composites (ECC) mixtures. The performance of RFA-ECC is assessed by evaluating the tensile properties at 7 days, for two replacement levels of ordinary portland cement (OPC) (50% and 70%) and three polyethylene (PE) fiber contents (1.5%, 1.75%, and 2% by volume fraction). Results showed that RFA-based ECC can produce strain-hardening behavior and reach high tensile stress and strain. RFA-ECC with 50% OPC replacement and 1.5 vol.% PE fiber content exhibits average tensile strength and strain of 6.4 MPa and 8.9%, respectively. Furthermore, at 28 days, the ductile behavior remains. The study shows that RFA can be considered an alternative low carbon constituent to replace OPC in ECC mixtures, to reduce their carbon footprint, hence leading to a more sustainable cementitious composite.